Gloss on the Judgment of the German Federal Labor Court (Bundesarbeitsgericht) of 24 October 2018, Case 10 AZR 69/18, Previous Instance Regional Labor Court (Landesarbeitsgericht) Hamburg, Judgment of 30 August 2017, Case 5 Sa 21/17 - Schirrmacher, Carsten (Studia Prawa Publicznego, 2025)
On 24 October 2018, the Federal Labor Court ruled that a “legal pro- tection secretary” employed by a trade union who advised trade union members on labor law issues could not be admitted to the bar. He lacked the professional independence required by the Federal Lawyers’ Act because, according to his employment contract, he had to respect the ideals of the trade unions. Although the employer had never given the legal protection secretary any instructions as to how he was to advise clients, the employer was also not obliged to confirm to the bar association that the legal protection secretary was carrying out his advisory work independently. The ruling, which is much discussed in Germany, raises the fundamental and still unresolved question of under what circumstances a legal advisor is “professionally independent.” This not only concerns the German legal landscape, but is particularly difficult to answer under German law because the legal situation is paradoxical: the German legislator itself allows employees access to the legal profession. The fact that a legal advisor is hired as an employee therefore does not automatically eliminate their professional independence. But what else? This gloss aims to contribute to this discussion.